Ciclagem de carbono em área sob semeadura direta e aplicação de lodo de esgoto - Freiberger, Mariângela Brito [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The study had as main objective to evaluate carbon (C) stock, changes in the amount of microbial C, quality of the soil organic matter (SOM) and CO2 emission as affected by sewage sludge applications in area under no-till. The experimental area, which shows a clayey Rhodic Ferralsol and is located in Botucatu, SP, has been conducted with the same treatments since 2002. The results of the present study, however, were obtained in the period from October 2012 to October 2014. A complete randomized blocks design arranged in a 2x4 factorial scheme and with four replicates was used. The treatments are represented by biennial application of two sewage sludge types (biodigested sludge - BS and centrifuged sludge - CS) in four rates: 0, 2, 4 and 8 Mg ha-1 (dry basis). The cropping system used in the study was a soybean/black oat succession. Yield and nutritional aspects of crops and CO2 emissions from soil were evaluated in each one of the cultivations. At the end of the study, soil samples were collected for analysis of soil fertility, OM fractionation, microbial C and C stock. The continued application of CS increased the pH and macronutrient levels in the soil, mainly Ca, as well as increased dry matter production and nutrient accumulation in aerial part of black oat. CS application also promoted greater accumulation of C in plants and greater activity of soil microorganisms, which led to a greater level of microbial biomass C (up to 390 mg kg-1 in the superficial layer), greater decomposition of light OM and consequently greater CO2 fluxes to the atmosphere (from 4.8 to 6.2 µmol m-2 s-1). Long time applications of sewage sludge (either BS or CS) resulted in increase of micronutrients levels in the soil, up to the point of Cu, Fe, Mn and Zn reach levels that may be harmful to plants. The soybean yield was higher (up to 3,232 kg ha-1) when sludge rates equivalent to 4.5 to 5.3 Mg ha-1 were used. The long-term application of sewage sludge increases the levels of total organic C (up 19.8 g kg-1), particulate fraction of C (up to 0.88 g kg-1) and C associated with minerals (up 19.0 g kg-1) only in the superficial layers of soil. Among the humic substances, the fraction that most contributed to the soil organic C (up 13.8 g kg-1) was humin. After six sewage sludge applications, regardless of the rate and type of sludge, the soil C stock increased only in the surface layer, and in total corresponded to 106.2 Mg ha-1.

O estudo teve por principal objetivo avaliar o estoque de carbono (C), as alterações na quantidade de C microbiano, a qualidade da matéria orgânica (MO) e a emissão de CO2 em decorrência de aplicações de lodos de esgoto em área sob semeadura direta. A área experimental, que apresenta Latossolo Vermelho de textura argilosa e está localizada em Botucatu, SP, tem sido conduzida com os mesmos tratamentos desde 2002. Os resultados constantes no presente estudo, entretanto, foram obtidos no período de outubro de 2012 a outubro de 2014. O delineamento experimental utilizado foi o de blocos ao acaso em esquema fatorial 2 x 4, com quatro repetições. Os tratamentos correspondem à aplicação bienal de dois resíduos (lodo biodigerido – LB e lodo centrifugado – LC) em quatro doses: 0, 2, 4 e 8 Mg ha-1 (base seca) e o sistema de produção utilizado nesse período foi a sucessão soja / aveia-preta. Em cada um dos cultivos avaliou-se características nutricionais e de produtividade das culturas e a emissão de CO2 a partir do solo. Ao final do estudo foram coletadas amostras de solo para análise química básica, fracionamento da MO, C microbiano e estoque de C. A aplicação continuada de LC promoveu aumento do pH do solo e do teor de macronutrientes, principalmente Ca, bem como maior produção de matéria seca e acúmulo de nutrientes na parte aérea da aveia-preta. O LC também promoveu maior acúmulo de C nas plantas e maior atividade dos microrganismos do solo, o que acarretou em maior teor de C da biomassa microbiana (até 390 mg kg-1 na camada superficial), maior decomposição de MO leve e, consequente maior fluxo de CO2 para atmosfera (de 4,8 a 6,2 µmol m-2 s-1). Aplicações de longa data de lodo de esgoto (LB ou LC) resultam no aumento do teor de micronutrientes no solo, a ponto de Cu, Fe, Mn e Zn se apresentarem em níveis que podem ser prejudiciais às plantas. A produtividade da soja foi maior (até 3.232 kg ha-1) quando do uso de doses de lodos equivalentes a 4,5 a 5,3 Mg ha-1. A aplicação de lodos de esgoto resulta em aumento dos teores de C orgânico total (até 19,8 g kg-1), C da fração particulada (até 0,88 g kg-1) e C associado a minerais (até 19,0 g kg-1) somente na camada superficial do solo. Dentre as substâncias húmicas, a fração humina foi a que mais contribuiu com o estoque de C no solo (até 13,8 g kg-1). Após seis aplicações de lodo de esgoto, independentemente da dose e tipo de lodo, o estoque de C no solo aumentou apenas na camada superficial, e correspondeu a 106,2 Mg ha-1.
Carbon cycling in an area under no-till and long-term sewage sludge application
Keywords: CO2 emission; Microbial carbon; Soil carbon storage; Soil organic matter fractionation; Emissão de CO2; Carbono microbiano; Estoque de carbono no solo; Fracionamento da matéria orgânica do solo